HUBUNGAN KECEPATAN DAN KELENTURAN OTOT PUNGGUNG DENGAN HASIL LOMPAT JAUH GAYA SCHNEPPER PADA MAHASISWA PENJASKESREK A PUTRA ANGKATAN 2014 UNIVERSITAS RIAU - Andrian, M. Juni; ', Ramadi; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem in this research is whether there is a correlation of speed and muscle flexibility with style schnepper long jump result. The goal is to find out how big correlation of speed and muscle flexibility with style schnepper long jump result. The technique of sampling is performed with total sampling of 27 people of university student class of 2014 Penjaskesrek A  of Riau University.. This research is using a correlation technique. Then, the data are tested using the test of normality, the product moment correlation test, test of significance on the level of significance of α = 0.05. Testing normality of variabels X1, L0maks (0,114) < Ltabel (0,161), Testing normality of variabels X2, L0maks (0,079) < Ltabel (0,161), and testing normality of variabels Y, L0maks (0,158) < Ltabel (0,161), in other words at a confidence level is 95% of normal data and research conclusion showed : there is a significant correlation between speed and muscle flexibility with style schnepper long jump result, with correlation r = 0,879, where rhitung >  rtabel or 0,879 > 0,381. and the relation is categorized strong. Therefore, Ho rejected and Ha accepted. Key Words :  Speed, muscle flexibility, style schnepper long jump result.